Bacteriophages and related endolysins for reduction of microorganisms in the human body - a systematic review - Özal, Dilara; Arndt, Andreas; Thomé, Marcus (German Medical Science GMS Publishing House, 2022)
Background: In recent years, resistance to antibiotics has become a global threat, and alternatives to antibiotics have become an area of research. The main alternative methods are briefly described in this review. However, the main focus is bacteriophage-related therapy. Bacteriophages are viruses which, due to the production of the enzyme endolysin, are able to kill bacterial host cells. Bacteriophage therapies have a long tradition. Their potential to function as antibiotics lies in their bactericidal activity and specificity in killing bacteria without infecting or affecting eukaryotic cells. Objective: To systematically review the outcomes of bacteriophage therapy in patients with bacterial infections.Methods: The MEDLINE, EMBASE, Web of Science and CENTRAL databases were searched electronically using search terms referring to bacteriophages, endolysins and antimicrobial resistance. After the literature was screened for their titles and abstracts, full-text reviews considering inclusion/exclusion criteria were performed. Data concerning patients with bacterial infections, treatment with either bacteriophages or its enzyme endolysin and their outcomes were extracted and analysed. Results: Thirteen publications were identified that met all inclusion criteria. Data extraction shows that bacteriophages or endolysins have the potential to combat bacterial infections and significantly reduce inflammatory mediators. However, 3 out of 4 randomized controlled trials revealed that there was no significant difference between phage/endolysin treated patients and control group. Significant clinical improvements were seen in cohort and case studies. A few minor side effects were reported. Conclusions: Although there are countries in which bacteriophages are prescribed as an alternative to established antibiotics, this valuable experience has yet to be examined sufficiently in clinical trials conducted to modern standards. Despite improvements in symptoms shown in the reviewed clinical trials, the infection and the bacteria themselves were rarely completely eradicated. Therefore, no definite answer can be given as to effectiveness, and further clinical trials are necessary.